Promontory Electrocochleography Recordings to Predict Speech-Perception Performance in Cochlear Implant Recipients. Issue 8 (19th September 2022) - Walia, Amit; Shew, Matthew A.; Lee, David S.; Lefler, Shannon M.; Kallogjeri, Dorina; Wick, Cameron C.; Durakovic, Nedim; Fitzpatrick, Douglas C.; Ortmann, Amanda J.; Herzog, Jacques A.; Buchman, Craig A.
Abstract : Objective: 1) To determine the relationship of electrocochleography (ECochG) responses measured on the promontory with responses measured at the round window (RW) and various intracochlear sites. 2) To evaluate if promontory ECochG responses correlate with postoperative speech-perception performance using the cochlear implant (CI). Study Design: Prospective cohort study. Setting: Tertiary referral center. Patients and Interventions: Ninety-six adult CI recipients with no cochlear malformations or previous otologic surgery. Main Outcome Measure(s): Acoustically evoked ECochG responses were measured intraoperatively at both extracochlear and intracochlear locations. ECochG total response (ECochG-TR), a measure of residual cochlear function, was calculated by summing the fast Fourier transformation amplitudes in response to 250-Hz to 2-kHz acoustic stimuli. Speech-perception performance was measured at 3 months. Results: There were strong linear correlations for promontory ECochG-TR with the ECochG-TRs measured at the RW ( r = 0.95), just inside scala tympani ( r = 0.91), and after full insertion ( r = 0.83). For an individual subject, the morphology of the ECochG response was similar in character across all positions; however, the response amplitude increased from promontory to RW (~1.6-fold) to just inside scala tympani (~2.6-fold), with the largest response at full insertion (~13.1-fold). Promontory ECochG-TR independently explained 51.8% of the variability ( r 2 ) in consonant-nucleus-consonant at 3 months. Conclusions: Promontory ECochG recordings are strongly correlated with responses previously recorded at extracochlear and intracochlear sites and explain a substantial portion of the variability in CI performance. These findings are a critical step in supporting translation of transtympanic ECochG into the clinic preoperatively to help predict postoperative CI performance.